Estimating influenza disease burden among pregnant women: Application of self-control method. Issue 36 (24th August 2017) - Ohfuji, Satoko; Deguchi, Masaaki; Tachibana, Daisuke; Koyama, Masayasu; Takagi, Tetsu; Yoshioka, Takayuki; Urae, Akinori; Fukushima, Wakaba; Hirota, Yoshio; ,
Highlights: Self-control method applied to evaluate influenza disease burden during pregnancy. Hospitalization rate due to respiratory illnesses was higher during pregnancy. Self-control method is useful for evaluating disease burden during pregnancy. Abstract: To evaluate influenza disease burden among pregnant women, an epidemiological study using the self-control method was conducted. Study subjects were 12, 838 pregnant women who visited collaborating maternity hospitals and clinics in Osaka Prefecture, Japan, before the 2013/14 influenza season. As a study outcome, hospitalization due to respiratory illnesses between the 2010/11 and 2013/14 seasons was collected from each study subject through a baseline survey at the time of recruitment and a second survey after the 2013/14 season. The hospitalization rates during pregnancy and non-pregnancy periods was calculated separately. To compare the hospitalization rate during pregnancy with that during non-pregnancy within the same single study subject, Mantel-Haenzel rate ratios (RRMH ) were calculated. During the four seasons examined in this study, nine and 17 subjects were hospitalized due to respiratory illnesses during pregnancy and non-pregnancy periods, respectively. The hospitalization rate was 2.54 per 10, 000 woman-months during pregnancy and 1.08 per 10, 000 woman-months during non-pregnancy. The RRMH for the hospitalization rate during pregnancy compared with that during non-pregnancy was 4.30 (95% confidence interval, 1.96–9.41). Our results suggest that during the influenza season, pregnant women have a higher risk than non-pregnant women for hospitalization due to respiratory illnesses. The self-control method appears to be an appropriate epidemiological method for evaluating the disease burden of influenza among pregnant women.